2017
DOI: 10.1590/1678-4685-gmb-2016-0043
|View full text |Cite
|
Sign up to set email alerts
|

New biotechnological tools to accelerate scab-resistance trait transfer to apple

Abstract: Apple is a fruit crop cultivated worldwide. Apple orchards are exposed to a diverse set of environmental and biological factors that affect the productivity and sustainability of the culture. Many of the efforts and costs for apple production rely on reducing the incidence of fungal diseases, and one of the main diseases is apple scab caused by the fungus Venturia inaequalis. The economic impact of scab on apple productivity has guided many breeding programs to search for cultivars resistant to apple scab. Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…One of the strategies adopted for disease management in apple is the genetic production of resistant cisgenic lines. The use of a virus‐based system that utilises a plant episomal expression vector (Li et al ., ) was successful in increasing the resistance of the susceptible apple cultivar ‘Gala Galaxy’ via the insertion of a scab resistance gene (Vanblaere et al ., ; Cusin et al ., ). Similarly, homologous expression of apple CNL in susceptible cultivars is expected to produce resistant traits.…”
Section: Discussionmentioning
confidence: 97%
“…One of the strategies adopted for disease management in apple is the genetic production of resistant cisgenic lines. The use of a virus‐based system that utilises a plant episomal expression vector (Li et al ., ) was successful in increasing the resistance of the susceptible apple cultivar ‘Gala Galaxy’ via the insertion of a scab resistance gene (Vanblaere et al ., ; Cusin et al ., ). Similarly, homologous expression of apple CNL in susceptible cultivars is expected to produce resistant traits.…”
Section: Discussionmentioning
confidence: 97%
“…The authors named this minimal viral construct p1470 and demonstrated its ability to deliver marker genes. So far, the IL-60 vector system has been successfully used in over 40 plant species belonging to 14 different families including perennial woody plants, such as orange, apple, and grape (Peretz et al, 2007;Cusin, Revers and Maraschin, 2017;Malabarba et al, 2018). The vector was introduced into the plants via root infiltration or by syringe inoculation.…”
Section: Dna Virus-based Delivery Systemmentioning
confidence: 99%
“…In a single apple-growing season, multiple cycles of conidiospore production and secondary infections occurs 13 . The control of the disease relies mainly on multiple fungicides spray 14 , which exhibit toxic effect to human health and may even contaminate the environment. Moreover, extended use of scab controlling fungicides may result in selection pressure on the V .…”
Section: Introductionmentioning
confidence: 99%